Elucidation of the Roles of Metal Ions in Misfolding and Aggregation of Pathogenic TTR Variants Associated with ATTR Amyloidosis - Irving, Robert (East Carolina University)
Transthyretin (TTR) is a homo-tetrameric transport protein that is responsible for carrying the thyroid hormone, thyroxine (T4) and retinol (vitamin A1) via retinol binding protein in both human plasma and cerebrospinal fluid. The native TTR tetramer is highly stable but can be destabilized under certain conditions such as single-point mutations, acidic pH, and elevated metal concentrations. Destabilization of the tetramer results in its dissociation into monomers leading to misfolding, aggregation, and amyloid fibril deposition in various soft tissue organs eventually causing a set of diseases with cardiomyopathic and neuropathic manifestations known as Transthyretin Amyloidosis (ATTR). The deposition of wild type derived amyloid fibrils leads to a non-hereditary form of ATTR known as ATTRwt. With symptoms manifesting as both polyneuropathic and cardiomyopathic, this condition affects approximately 25% of the male population above the age of 80 and is the primary cause of death for supercentenarians. However, it is the hereditary transthyretin amyloidosis (ATTRv), caused by significantly increased rates of aggregation due to single point mutations, that are of particular concern. There are over 120 amyloidogenic variants of TTR that significantly increase the pathogenicity of TTR aggregation. These variants are primarily cardiomyopathy and polyneuropathy causing, though many variants lead to amyloidosis with mixed phenotype. In addition to this, many patients with either cardiomyopathy or polyneuropathy report ocular, GIT, and renopathic manifestations along with their primary phenotype. The most aggressive TTR variants cause significant damage to the central nervous system, leading to progressive dementia, ataxia, and stroke-like symptoms. Two TTR variants will be investigated in this study. The variant L55P, which replaces the lysine at position 55 with a proline, is the most pathogenic TTR mutation and often manifests with mixed phenotypes leading to varying combinations of cardiomyopathic and polyneuropathic symptoms. The variant V122I, replacing the valine at position 122 with an isoleucine is the most common mutation in the United States, carried by approximately 4% of African Americans and is primarily cardiomyopathy causing. With the presence of zinc found in ocular TTR amyloid extracts and microcalcification in cardiac extracts, it has been theorized that these physiological metals may play a more key role in ATTR pathogenesis, like those in Alzheimer's related proteins. As such, experiments were developed to observe the effect zinc and calcium on TTR aggregation under physiological pH. Understanding the roles these metals play in vitro can offer insight into what might be occurring in vivo. Additionally, since there are currently only therapies associated with stabilizing the native TTR tetramer, determining other factors in TTR amyloid formation can create opportunities for multiple approaches to treatment.
Keywords: chemistry; transthyretin; Carrier proteins; Protein folding; Thermodynamics; Metals--Isotopes